Comparative efficacy and safety of botanical drugs for mild cognitive impairment: a systematic review and network meta-analysis - Yang, Yifan; Wang, Haixia; Lü, Jianmeng; Zhang, Hui; Wang, Tao; Yan, Yongmei (Frontiers in Pharmacology, 2025)
ObjectiveThis study evaluated the comparative efficacy and safety of eighteen botanical drug interventions in improving cognitive function, daily living activities, and psychological wellbeing in patients with mild cognitive impairment (MCI).MethodsRandomized controlled trials were identified from PubMed, Embase, Cochrane Library, and Web of Science up to September 2025. Methodological quality was assessed using the Cochrane Risk of Bias tool, and data were analyzed within a Bayesian framework.ResultsNineteen trials involving 4,956 participants were included. For cognitive function, measured as a standardized mean difference (SMD) to harmonize various assessment scales, Pycnogenol showed the most significant effect and the highest probability of being the best intervention (Surface Under the Cumulative Ranking Curve, SUCRA: 98.8%). It also ranked highest for improving daily living (SUCRA: 100%), whereas Cosmos caudatus Supplement ranked first for psychological wellbeing (SUCRA: 98.9%). Most included botanical drugs were generally well-tolerated, with adverse event rates comparable to placebo, although safety reporting was inconsistent across studies.ConclusionPycnogenol showed the highest probability of improving cognitive function and daily living scores in patients with MCI, while Cosmos caudatus supplementation ranked highest for psychological outcomes. Although these findings highlight potential benefits, heterogeneity among the included studies warrant cautious interpretation.